An Adaptive Fading CKF-Based Method for Estimating the Line of Sight Rate with Strapdown Seeker - Xia, Shuhan; Fan, Junfang; Huang, Jiaqi; Ji, Yi; Pei, Pei (Chinese Automation Congress (Online), 2023)
Due to the coupling effect of attitude angles, the extraction of line-of-sight angular rate in the terminal guidance stage of low-cost guided munitions is often inaccurate. To address this issue, this paper proposes an estimation method for line-of-sight angular rate based on adaptive fading CKF, which eliminates the coupling effect of body attitude angular rate. The mathematical model of the line-of-sight angle is established to derive the estimation model of the line-of-sight angular rate. Different from the basic method, this paper uses an adaptive fading CKF and introduce a fading factor based on residual sequence to adjust the predicted state covariance. In order to show the superiority of our proposed method, this paper conduct comparative simulation experiments with the line-of-sight angular rate estimation methods based on EKF and classical CKF, the results indicate that AF-CKF has better filtering performance.